The Effect of Heating Schedule on Physico-Chemical Properties of Instant Coffee of Liberika Tungkal Jambi - Mursalin, Mursalin; Nizori, Addion; Rahmayani, Irma (Indonesian Food Science and Technology Journal, 2019)
Abstract— The making of instant brewed coffee using co-crystallization method is strongly influenced by the heating schedule (HS) applied. Five levels of HS (HS1, HS2, HS3, HS4 and HS5) were studied on the physico-chemical properties of instant coffee of Liberika Tungkal Jambi. The treatment was applied in a completely randomized design with 4 replications. The coffee was extracted using a special coffee extractor in a ratio of hot water/coffee powder of 15/1. Parameters observed were moisture content, ash content, pH, solubility, and total dissolved solids. The data obtained were analyzed using ANOVA and DNMRT at 5% significance. The results showed that the physico-chemical properties of instant coffee had significant effect on moisture content, pH, solubility, and total dissolved solids but not on ash content. The optimal HS to produce Liberika Tungkal Jambi instant coffee with good quality was heating at 110oC in the beginning, followed by 90oC at the initiation of crystallization, and 75oC when crystal growth (HS3). HS3 produces instant coffee with water content 1.57-1.61%; ash content 6.12-6.16; pH 5.50-5.56; solubility 98.22-98.25; and total dissolved solids 8.47-8.53% Brix. Keywords— crystal growth,instant coffee, libtukom, recrystallization,